Analisis Keterampilan Riset Mahasiswa Melalui Karya Ilmiah Pada Mata Kuliah Bioteknologi Dengan Model Project Base Learning - Sayekti, Titah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The 21st century learning trend emphasizes skills, not just knowledge. Among the emerging competencies are learning and innovation, which are very possible to be accommodated at the higher education level. In order to realize this, research skills are an important competency that must be possessed by students and are the outlet of the studies carried out. This study is a quantitative descriptive study that analyzes research skills in students' scientific work which is the output of the biotechnology course. The research skills aspect is based on the Research Skill Development (RSD) developed by Willison and O'Regan which has been modified. Based on the results of the analysis of scientific work which is the output of the biotechnology course, students achieved a score of 81 with a very good category. However, there are several aspects that still need to be strengthened. The lowest aspect of research skills is presenting problems, namely with a score of 2.0 and is categorized as lacking. The aspect that is also categorized as lacking is literature search which strengthens the analysis with a score of 2.2. Students need to strengthen their skills in literature search as an effort to deepen their findings. Further research can be directed at the implementation of problem-based learning combined with science writing heuristic as an effort to strengthen the aspects of problem presentation and literature search in research skills.